THE CONTRIBUTION OF ENGLISH COMPETENCYON WORKING READINESS OF FOOD AND BEVERAGE PRODUCTSTUDENTS - Tari, Nirmala; Dianita Safitri, Ni Putu; Oktaviani, Laras (Akademi Komunitas MAPINDO, 2020)
This research aims at knowing the contribution of English competency on working readiness of Food and Beverage Product students in Akademi Komunitas MAPINDO. This research applies the correlational research design. To run this research, 30 students were selected as sample taken from two classes, TB A and TB B. The data of English Competency were collected directly from English instructor report; and students’ readiness were collected by using a questionnaire with Likert scale. The obtained data were then analyzed by using Pearson Product Moment correlation and Multiple Regression with one predictor formulas. This research discovers that both partially and simultaneously there is a significant effect of English competency on working readiness of food and beverage product students in Akademi Komunitas MAPINDO. English is very important to improve the students’ readiness in working through the hospitality industry. For that reason, it is suggested for the campus to improve students’ English competency, to be hard workers. Keywords: English Competency and Working Readiness